Detecting COVID-19-Related Fake News Using Feature Extraction - Khan, Suleman; Hakak, Saqib; Deepa, N.; Prabadevi, B.; Dev, Kapal; Trelova, Silvia (Frontiers in Public Health, 2022)
Since its inception in December 2019, there have been numerous posts and news regarding the covid-19 pandemic in social media, traditional print, and electronic media. These sources have information from both trusted and non-trusted medical sources. Furthermore, the news from this medium is spread rapidly. Spreading a piece of deceptive information may lead to anxiety, unwanted exposure to medical remedies, tricks for digital marketing and may lead to deadly factors. Therefore, a model for detecting fake news from the news pool is very essential. In this work, the dataset which is a fusion of news related to covid-19 that has been sourced from data from several social media and news sources is used for classification. In the first step, preprocessing is performed on the dataset to remove unwanted text, then tokenization is carried out to extract the tokens from the raw text data collected from various sources. Later, feature selection is performed to avoid the computational overhead incurred in processing all the features in the dataset. The linguistic and sentiment features are extracted for further processing. Finally, several state-of-the-art machine learning algorithms are trained to classify the covid-19 related dataset. These algorithms are then evaluated using various metrics. The results show that the Random Forest classifier outperforms the other classifiers with an accuracy of 88.50%.